(untitled) - FAO (Rome, 2000)
The book presents the principles that have been followed, detailling the measures taken and the results achievement to date; FAO's structure, govermance mechanisms and operational and financial procedures has lent a much greater degree of coherence to our wide-ranging and multidisplinary activities. The book also has led to a strategic vision for the future.
Keywords: agriculture - research